The emerging use of Twitter by urological journals. (23rd October 2014) - Nason, Gregory J.; O'Kelly, Fardod; Kelly, Michael E.; Phelan, Nigel; Manecksha, Rustom P.; Lawrentschuk, Nathan; Murphy, Declan G.
<x xml:space="preserve">Abstract</x> Objective To assess the emerging use of Twitter by urological journals. Methods A search of the Journal of Citation Reports 2012 was performed to identify urological journals. These journals were then searched on Twitter.com. Each journal website was accessed for links to social media (SoMe). The number of 'tweets', followers and age of profile was determined. To evaluate the content, over a 6‐month period (November 2013 to April 2014), all tweets were scrutinised on the journals Twitter profiles. To assess SoMe influence, the Klout score of each journal was also calculated. Results In all, 33 urological journals were identified. Eight (24.2%) had Twitter profiles. The mean (range) number of tweets and followers was 557 (19–1809) and 1845 (82–3692), respectively. The mean (range) age of the twitter profiles was 952 (314–1758) days with an average 0.88 tweets/day. A Twitter profile was associated with a higher mean impact factor of the journal (mean [sd] 3.588 [3.05] vs 1.78 [0.99], P = 0.013). Over a 6‐month period, November 2013 to April 2014, the median (range) number of tweets per profile was 82 (2–415) and the median (range) number of articles linked to tweets was 73 (0–336). Of these 710 articles, 152 were Level 1 evidence‐based articles, 101 Level 2, 278 Level 3 and 179 Level 4. The median (range) Klout score was 47 (19–58). The Klout scores of major journals did not exactly mirror their impact factors. Conclusion SoMe is increasingly becoming an adjunct to traditional teaching methods, due to its convenient and user‐friendly platform. Recently, many of the leading urological journals have used Twitter to highlight significant articles of interest to readers.